2010
DOI: 10.1007/s12595-010-0003-7
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito species composition of the Dooars of West Bengal, India

Abstract: The sub Himalayan Dooars belt of Jalpaiguri district in West Bengal is an endemic focal area for malaria. A survey of mosquitoes was conducted from four sites of the Central Dooars during 2006 -07. The sampling sites were at Nagrakata, Binnaguri, Ballaguri, and Totopara. The different endophilic mosquito species recorded from hutments and tea garden dwellings Armigeres subalbatus and Toxorhynchites splendens. Per man-hour density (PMD) of all species were determined for the mosquitoes species. Besides a genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…They also reported that the evenness components varied greatly, ranging from 54.03 to 95.03% in this region. In the same year, mosquitoes were surveyed from Nagrakata, Binnaguri, Ballaguri and Totopara in the central dooars [18] . In this study, 16 mosquito species were found in human habitation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They also reported that the evenness components varied greatly, ranging from 54.03 to 95.03% in this region. In the same year, mosquitoes were surveyed from Nagrakata, Binnaguri, Ballaguri and Totopara in the central dooars [18] . In this study, 16 mosquito species were found in human habitation.…”
Section: Resultsmentioning
confidence: 99%
“…Anopheles aitkenii [16] 27. Anopheles barbirostris [16][17][18] 28. Anopheles hyrcanus [16,17,18] 29.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…minimus and An. baimaii are predominantly available vector species [24]; there quantity is lowering down [25]. Besides, these are replaced by A. culicifacies in their locations [26].…”
Section: Biodiversitymentioning
confidence: 99%